A Comparative Study of Optical Sensing Methods for Colourimetric Bio/Chemical Detection: Cost, Scale, and Performance - Cormac D. Fay; Liang Wu; Isabel M. Perez de Vargas Sansalvador (Sensors, 2025)
This study provides a detailed comparison of three optical sensing approaches for colourimetric bio/chemical detection, focusing on cost, scalability, and performance. We examine laboratory-grade spectrophotometry, portable camera-based imaging, and low-cost LED photometry using Paired Emitter–Detector Diode (PEDD) charge–discharge methodology. Our findings reveal that while the LED-based PEDD system outperforms the other two methods in key sensory metrics—such as sensitivity, resolution, and limit of detection—its cost-effectiveness and scalability make it a promising solution for widespread industrial and field applications. Compared to the spectrophotometer, the LED/PEDD approach demonstrates improvements in measurement range (×16.39), dynamic range (×147.06), accuracy (×1.79), and sensitivity (×107.53). The results highlight the potential for industrial-scale adoption of LED photometry, especially for cost-effective applications in bio/chemical sensing sectors.